Beyond the Degree: Fertility Outcomes of 'First in Family' Graduates - Anna Adamecz; Anna Lovász; Suncica Vujic (Institute of Labor Economics (IZA), 2024)
This paper looks at the relationship between higher education and fertility, focusing on how intergenerational educational mobility shapes this dynamic. Using the 1970 British Cohort Study, we estimate gaps in completed fertility, distinguishing between those who are the first in their family to graduate from a university (FiF), graduates with a graduate parent, and non-graduates. Our findings reveal that while on average, graduate women have fewer children than non-graduates, this difference is driven by FiF graduates. FiF women tend to have fewer children than both non-FiF graduates and non-graduates, who exhibit similar fertility rates. The fertility gap between FiF and non-FiF graduates emerges after age 35, mainly on the extensive margin: FiF women are more likely to remain childless, but those who become mothers have an equal average number of children. Similar patterns are observed among men, although the gaps are smaller and not statistically significant. We identify child-related preferences, self-esteem, and maternal employment in childhood as potential explanations behind the FiF fertility gap, while labour market outcomes, financial constraints, partnerships, and health do not appear to play a role. These findings underscore important considerations for supporting inter-generational mobility and fertility.
Keywords: I26; J13; J16; J24; 330; first in family graduates; fertility; childlessness; inter-generational educational mobility; gender economics